Human development 10/11 (New York ; London : McGraw-Hill Higher Education ; McGraw-Hill, 2011)
Provides an access to a wide range of articles from some of the respected magazines, newspapers, and journals published. This title has a number of common organizational features designed to make them particularly useful in the classroom: a general introduction; an annotated table of contents; a topic guide; and, an overview for each section.
Keywords: Developmental psychology -- Periodicals; Life cycle, Human -- Periodicals